Optimal presale strategy under the deposit inflation mode: Ordinary or sinking strategy - Weier Situ; Yongqing Zhang; Xiting Lyu; Wei Zhang (PLoS ONE, 2025)
In the context of the rapid development of e-commerce, the advanced selling strategy has become an important means widely used by online retailers, and the innovation of this advanced selling strategy has been extended to the logistics service level. Based on the consumer utility theory, combined with the strategic behavior of consumers, this paper compares the advantages and disadvantages of ordinary pre-sale strategy (OPS) and sinking pre-sale strategy (SPS) under the deposit inflation mode. The research results show that when consumers have a high level of awareness of logistics services and a moderate proportion of tail payment, the sunken pre-sale strategy has more advantages, and the improvement of consumers’ perception coefficient of logistics, proportion of tail payment, and SPS logistics speed is conducive to the increase of retailers’ profits. In addition, retailers need to be cautious when setting pre-sale prices and deposits to avoid excessive deposit settings leading to the loss of consumers. Regardless of the inflation factor of the deposit, the amount of payment remains unchanged, but the higher coefficient helps to increase demand and profit. The research not only provides theoretical support for retailers in formulating advanced selling strategies but also reveals the close relationship between consumer behavior and the market.